Carbamylation is Instrumental in End-Stage Kidney Disease Coagulopathies: The Impact on von Willebrand Factor and Platelet Functionality - Babickova, Janka; Kałucka, Urszula; Sochaj-Grzegorczyk, Alicja; Potempa, Jan; Scavenius, Carsten; Knoop, Thomas; Marti, Hans-Peter; Kaminska, Marta; Mydel, Piotr (Thrombosis and Haemostasis, 2024)
Background Chronic kidney disease (CKD) is a progressive, irreversible, and incurable condition characterized by high morbidity and mortality, affecting approximately one-tenth of the global population. Rise of urea-derived cyanate levels in CKD patients, severalfold higher in comparison to those found in healthy individuals, leads to an increased rate of carbamylation of lysine residues of proteins and peptides. This posttranslational modification plays an important role in the progression of kidney failure but also in the onset of CKD-related complications, including previously reported coagulopathies. In this study, we have explored the impact of carbamylation on the functionality of von Willebrand factor (vWF), a pivotal player in hemostasis, and its implications for platelet adhesion.Materials and Methods We have explored carbamylated vWF's interactions with its partner proteins via ELISA. Mass spectrometry was employed to identify modified lysine residues. Blood platelets isolated from healthy donors were carbamylated, and their activation, binding to endothelium and thromboxane release were evaluated using flow cytometry, adhesion assays and ELISA, respectively.Results Using mass spectrometry we detected the vWF's lysine residue smost susceptible to carbamylation. This modification has in turn affected vWF's interactions with its key binding partners: decreased binding to collagen types I/III but increased the affinity to factor FVIII, while its binding to fibrinogen remained unchanged. Carbamylation of vWF impeded vWF-blood platelet binding, but carbamylation of platelets led to their increased thrombin-dependent activation as observed by enhanced phosphatidylserine exposure, improved their binding to vascular endothelium, at the same time decreasing the production of the prothrombotic mediator, thromboxane A2.Conclusion Our findings highlight the multifaceted impact of carbamylation on vWF and platelets, disturbing the delicate balance of coagulation cascade. These alterations could contribute to the complex hemostatic imbalance in ESKD, underscoring the need for further research to fully understand these mechanisms and their clinical implications.
Keywords: carbamylation; von Willebrand factor; coagulation; platelet; chronic kidney disease